Facile synthesis of highly disperse Ni–Co nanoparticles over mesoporous silica for enhanced methane dry reforming. Issue 14 (21st March 2018) - Das, Subhasis; Sengupta, Manideepa; Bag, Arijit; Shah, Mumtaj; Bordoloi, Ankur
Abstract : A synergistic approach was made to develop a highly stable and carbon resistant catalyst system based on cobalt and nickel supported over modified mesoporous silica for the dry reforming of methane (DRM). Abstract : A synergistic approach was made to develop a highly stable and carbon resistant catalyst system based on cobalt and nickel supported over modified mesoporous silica for the dry reforming of methane (DRM). Modified mesoporous silica is prepared by a hydrothermal method, and the total Co & Ni composition is taken at around 5% by using the deposition-precipitation technique. CO2 reforming with methane was performed at 400–800 °C under atmospheric pressure as well as at a pressure of 1 MPa, keeping the CH4 /CO2 ratio equal to unity. The catalyst assembly before and after the reaction was thoroughly characterized by a wide range of analytical techniques including N2 physisorption, XRD, TPR, TPO, TPH, XPS, SEM, TEM, elemental mapping, TG-DTG. The physicochemical characterization results confirmed the homogeneous distribution of nanosized metal particles into the hexagonal framework of modified silica, which plays a vital role towards a stronger metal support interaction that renders carbon deposition upon the active metal surface as well as avoids metal sintering at higher temperatures. At the same time, the coexistence of nanosized Co and Ni into the mesopores produced a synergy which provides better stability without any deactivation at high pressure reaction conditions. In situ DRIFT analysis evidenced that the reaction proceeds over these catalysts through an initial pathway in which both methane and carbon dioxide initially dissociate over the metal along with a bifunctional pathway in which methane dissociates over the active metal and carbon dioxide activated over the basic support surface via a formate intermediate. Density Functional Theory (DFT) calculations were also performed and further support the proposed mechanism from DRIFT studies.